Teratogenicity of retinoic acid and its effects on TGF-?2 expression in the developing cerebral cortex of the rat - Çolakoglu, N; Kükner, A (Springer, 2004)
Vitamin A metabolites are potent teratogens in a wide variety of species. including man. Transforming growth factor betas (TGF-betas) are involved in several mammalian prenatal developmental processes. The aim of this study was to determine the effects of exogenous and excessive all-trans retinoic acid on TGFbeta2 expression in the developing cerebral cortex of the rat. Man), of the malformations including exencephaly. exophtalmus. abdominal wall defects, extremity reduction defects observed in this study were dependent on the time of administration of retinoic acid. TGF-beta2 was diversely expressed, as revealed immunohistochemically. in the cerebral cortex and plexus choroideus. The diversity depended on the gestational day and the was affected by the administration of retinoic acid. In the 15-day-old fetus from mothers who had been fed by gavage a single dose of 60 mg/kg body weight of all-trans retinoic acid on the 8th day of gestation, TGF-beta2 immunoreactivity in the brain was decreased. However. by the 18th day of gestation, TGF-beta2 expression increased. The expression of TGF-beta2 in fetuses whose mothers had been given all-trans retinoic acid after the neurulation period (on day 12 of gestation) was generally similar to that in a control group. We conclude that all-trans retinoic acid leads to severe congenital malformations If administered before neurulation whereas if given after neurulation. it is not so teratogenic. Further. retinoic acid has a variable effect on the expression of TGF-beta2.
Keywords: Growth-Factor-Beta; Differential Regulation; Embryonic-Development; 13-Cis-Retinoic Acid; Mouse Embryo; Tgf-Beta; Organogenesis; Localization; Death; Cells